2018
DOI: 10.1093/nar/gky001
|View full text |Cite
|
Sign up to set email alerts
|

The cohesion establishment factor Esco1 acetylates α-tubulin to ensure proper spindle assembly in oocyte meiosis

Abstract: Esco1 has been reported to function as a cohesion establishment factor that mediates chromosome cohesion and segregation in mitotic cells. However, its exact roles in meiosis have not been clearly defined. Here, we document that Esco1 is expressed and localized to both the nucleus and cytoplasm during mouse oocyte meiotic maturation. Depletion of Esco1 by siRNA microinjection causes the meiotic progression arrest with a severe spindle abnormality and chromosome misalignment, which is coupled with a higher inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 41 publications
4
27
0
Order By: Relevance
“…Our previous studies reported that cohesin establishment factors, Esco1 and Esco2, regulate distinct functions during oocyte meiosis. Esco1 acetylates -tubulin to ensure microtubule stability to promote spindle assembly (42). Esco2 maintains H4K16 acetylation to participate in kinetochore functions for the SAC activity (43).…”
Section: Downloaded Frommentioning
confidence: 99%
“…Our previous studies reported that cohesin establishment factors, Esco1 and Esco2, regulate distinct functions during oocyte meiosis. Esco1 acetylates -tubulin to ensure microtubule stability to promote spindle assembly (42). Esco2 maintains H4K16 acetylation to participate in kinetochore functions for the SAC activity (43).…”
Section: Downloaded Frommentioning
confidence: 99%
“…For example, HDAC3 has been reported to affect the meiotic apparatus assembly by regulation of tubulin acetylation in mouse oocytes [ 15 ]. In addition, Esco1, which is involved in sister chromatid cohesion, acetylates α-tubulin to promote proper spindle assembly in meiosis [ 18 ]. In our study, we observed that a big proportion of spindle structure was destroyed after Kif18a KD, which correlated with a high tubulin acetylation level in comparison with the control oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, tubulin acetylation exists primarily for spindle stability in oocytes and embryos (de Pennart et al, ). It was also shown that decline in α‐tubulin acetylation resulted in fewer long‐lived RPE cell microtubules (Xu et al, ) and caused defective spindle assemblies and misaligned chromosomes in mouse oocytes (Lu et al, ). Our recent study showed that the KIF4a knockdown affected tubulin acetylation levels in mouse oocytes (Tang et al, ).…”
Section: Discussionmentioning
confidence: 99%